Adherence to iron deficiency interventions among pregnant women attending antenatal clinics in Ubungo municipality, Dar es Salaam, Tanzania - Glory Benjamin; Ezra J. Mrema; Nchang’wa Nhumba; Albert Burudi Wakoli; Hussein H. Mwanga (Bulletin of the National Research Centre)
Abstract Background Iron deficiency anemia in pregnant women remains a public health concern despite iron deficiency interventions that have been implemented. This study investigated adherence to iron deficiency interventions and the associated factors among pregnant women attending antenatal clinics in Ubungo Municipality. Methods This cross-sectional study used a systematic random sampling technique to obtain 503 participants from the surveyed clinics. Interviews were conducted by using interviewer-administered questionnaires. Data were analyzed using Stata version 17. The study employed binary and multivariable logistic regression analysis to determine factors associated with adherence to iron deficiency interventions. Results In this study, 72% of participants were non-adherent and 28% were adherent to the interventions. In multivariable regression analysis, participants who forgot to take their iron tables on most days (AOR 2.35; 95% CI 1.23–4.48) and those who reported that not enough time was spent on education and counseling during antenatal clinic visits (AOR 3.87; 95% CI 1.08–13.84) were more likely to be non-adherent to iron deficiency interventions. Conclusions Majority of pregnant women in Ubungo Municipality were non-adherent to iron deficiency interventions. Non-adherence was associated with a tendency to forget taking iron tablets, and lack of enough time in providing health education and counseling. Improving the quality of health education and counseling could increase adherence to iron deficiency interventions and reduce maternal–child morbidity and mortality rates.